Experimental studies of the bearing capacity of composite cross section beams made of pultrusion fiberglass rofile (PFP) - M. A. Salakhutdinov; D. N. Aripov; A. R. Khanekov (Vestnik MGSU)
Introduction. The article discusses the results of field tests of composite I-beam beam made of pultrusion fiberglass profiles (PSP) to assess their bearing capacity and deflections. The relevance of the study is due to the limited use of solid beams made of pultrusion fiberglass profiles for relatively large spans, which requires the use of composite beams. Constructive solutions have been developed for beams of composite I-section made of pultrusion fiberglass profiles, the belts of which are made of paired corners, with solid and perforated walls. Currently, there is no current regulatory documentation at the level of codes of practice or GOST, which provides a method for calculating the bearing capacity for composite sections made of PSP, especially beams with a perforated wall.Materials and methods. Experimental studies were performed on a three-point bend. During the field tests, vertical movements of the beams and wall deformations relative to the shelves were recorded.Results. According to the results of field tests, the bearing capacity, deflections, and composite I-beams with solid and perforated walls were determined. A comparative analysis with the results of experimental and numerical studies has been carried out.Conclusions. The significance of field tests is to assess the bearing capacity and deflections, beams of composite I-section made of pultrusion fiberglass profiles with three-point bending, the possibility of further development and improvement of their calculation methods.